Urban Flood Exposure and Vulnerability: Insights From Pendik District of Istanbul - Ozge Naz Pala; Irem Daloglu Cetinkaya; Mahir Yazar (Journal of Flood Risk Management)
ABSTRACT Cities striving to adapt to the impacts of climate change must recognize the significant variability in flood vulnerability across different communities. By examining the interplay between physical and socio‐demographic factors, this paper provides a comprehensive overview of the multidimensional aspects of flood exposure and vulnerability in Istanbul's Pendik District. The Pendik District, situated within the Istanbul Metropolitan Area, was chosen for this study as it regularly faces floods exacerbated by climate change. Utilizing a mixed‐methodology approach, ranging from the analytic hierarchy process (AHP) to surveys and census data, we find that areas classified as flood‐prone have residential units with lower land market values. Additionally, these high flood‐prone areas within the district tend to be populated by elderly individuals, refugees, and citizens with low education levels. In sum, this study reveals that there is a sharp correlation between socio‐economically disadvantaged communities and their exposure and vulnerability to urban flooding in Pendik District. As long as the current urban design and building stock fail to address the high level of flood exposure among the most disadvantaged urban communities, there is a critical need for inclusive urban planning and disaster management strategies.